The X-ray of the body in Yolanda Blanco’s poetry - Jiménez, Luis A. (2026)
The representation of the woman body in thepoetry of Nicaraguan author Yolanda Blanco is the mainobjective of this essay. By creating the equationbody=text in the book, the writer constructs a feministsubject in confrontation with the phallocentric values inWestern culture. We explore existing dichotomies in thepoetic discourse. At the same time and by means of thelunar cycles, we examine the themes that originate fromthese phases in the textual production.